(untitled) (Research, Society and Development, 2021)
The orderly development of cities requires planning actions in accordance with the conditions of the environment, its use and occupation. This study aims to analyze the use and occupation of land around the Mãe Bonifácia State Park (PEMB) in the city of Cuiabá/MT and the real estate valuation in the years 2005, 2010 and 2020. The properties studied are located in the Zona de Damping within a range of 150m from the park boundary. The study of the use and occupation of land and properties were analyzed based on information from spatial data via Google Earth-Street View and vector data provided by the Municipality of Cuiabá, as well as the Generic Values ​​Plant (PVG) and the Land Value of the Land (VVT), using geoprocessing in a Geographic Information Systems (GIS) environment. The results allowed us to analyze the structuring of the urban space where the highest real estate valuation was noticed in the properties close to the main avenues adjacent to the PEMB.